Iron parameters in pregnant women with beta‐thalassaemia minor combined with iron deficiency anaemia compared to pregnant women with iron deficiency anaemia alone demonstrate the safety of iron supplementation in beta‐thalassaemia minor during pregnancy. (25th September 2021) - Chen, Niankun; Li, Zhongjun; Huang, Yingying; Xiao, Chaoqun; Shen, Xinyang; Pan, Shumin; Su, Qiongqiong; Wang, Zhijian
Summary: In patients with beta‐thalassaemia intermedia or major, hepcidin induces iron overload by continuously promoting iron absorption. There have been no studies in pregnant women with beta‐thalassaemia minor combined with iron deficiency anaemia (IDA), examining whether hepcidin is inhibited by GDF15, as may occur in patients with beta‐thalassaemia intermedia or major, or whether the iron metabolism characteristics and the effect of iron supplementation are consistent with simple IDA in pregnancy. We compared and analysed routine blood parameters, iron metabolism parameters, the GDF15 levels, and the hepcidin levels among four groups, namely the beta‐thalassaemia (β) + IDA, β, IDA, and normal groups. In addition, the β + IDA and IDA groups received iron supplementation for four weeks. We found no statistically significant correlation between hepcidin and GDF15 in any group, but a positive correlation was observed between hepcidin and ferritin. After iron supplementation, the routine blood parameters and iron metabolism parameters in the β + IDA group were improved, and the hepcidin content was significantly increased. These results suggest that in pregnant women with beta‐thalassaemia minor, hepcidin functions normally to maintain iron homeostasis, and that iron supplementation is effective and safe.